Teaching online in Polish higher education institutions - Górak-Sosnowska, Katarzyna; Tomaszewska, Lidia (Przegląd Krytyczny, 2022)
This article presents the system of higher education (HE) in Poland and the role of remote (and later online) learning in education with the focus on changes induced as the response to the COVID-19 pandemic. The analysis begins with a historical background that shows how higher education has been changing after the political transformation of the 1989, and proceeds with a discussion about the conditions in which remote learning emerged. On the one hand, these conditions relate to the existing programmes that e-learning offers – the tools. On the other hand, they refer to the level of digital preparedness – the skills. The article is meant to be descriptive and combines didactic (both institutional and student-related) and administrative perspective of responding to COVID-19. The article analyses how the Polish HE system managed the transition to online teaching caused by the pandemic.